2020
DOI: 10.3390/plants10010027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Selected Rice Genotypes under Water Stress Conditions

Abstract: Drought is the most challenging abiotic stress for rice production in the world. Thus, developing new rice genotype tolerance to water scarcity is one of the best strategies to achieve and maximize high yield potential with water savings. The study aims to characterize 16 rice genotypes for grain and agronomic parameters under normal and drought stress conditions, and genetic differentiation, by determining specific DNA markers related to drought tolerance using Simple Sequence Repeats (SSR) markers and groupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
5
18
0
Order By: Relevance
“…Gramaje et al [25] observed Pearson's correlation and revealed that all of the yield component traits were positively correlated with grain yield. Genetic distance was correlated positively with grain length, panicle number and length: width ratio and correlated negatively with grain width, grain yield and seed setting rate [26,27]. Highly positive and significant phenotypic correlations were observed between yield index and leaf rolling, sterility percentage [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gramaje et al [25] observed Pearson's correlation and revealed that all of the yield component traits were positively correlated with grain yield. Genetic distance was correlated positively with grain length, panicle number and length: width ratio and correlated negatively with grain width, grain yield and seed setting rate [26,27]. Highly positive and significant phenotypic correlations were observed between yield index and leaf rolling, sterility percentage [28].…”
Section: Discussionmentioning
confidence: 99%
“…These genotypes are widely cultivated in Egypt because of desirable features such as their high yield and good taste. While the Giza178 cultivar (Indica/Japonica type) is resistant to blast and tolerant to drought, Sakha104 (Japonica type) is sensitive to both of them ( Gaballah et al, 2021 ). There is a need to explore other factors that might maximize the frequency of regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…This is equivalent to increasing rice production by 32.58 thousand tons annually. Recently, Gaballah et al [30] reported that Sakha101 and Giza179 were the best performing inbred genotypes in a study that was conducted under water stress conditions. On the other hand, the average water use efficiency for the cultivars under the current study was estimated to be 0.78 ton/thousand m 3 .…”
Section: Economic Indicators Of Land and Water Productivity Of Rice Cultivarsmentioning
confidence: 99%
“…An extra reduction in irrigation water could be achieved faster by the utilization of modern technologies and developing new cultivars that require comparatively fewer irrigations without any reduction in grain yield and quality traits [29]. Newly improved rice varieties hold great promise toward sustainable rice production in Egypt [30].…”
Section: Introductionmentioning
confidence: 99%